Study on combining ability for seed yield and its attributing traits in sunflower (Helianthus annuus L.): STUDY ON COMBINING ABILITY FOR SEED YIELD AND ITS ATTRIBUTING TRAITS IN SUNFLOWER - V B BAVAGE; S D NEHRU; M S UMA; M S UMAR FAROOQ (Journal of Oilseeds Research, 2021)
Six CMS lines and nine restorers ofsunflower were used in a Line × Tester mating design at Zonal Agricultural Research Station, Bengaluru to determine the combining ability and mode of gene action. The traits studied were days to 50 % flowering, plant height, head diameter, stem diameter, seed yield/plant, 100 seed weight, volume weight and oil content. The gca and sca effects were not significant for all the traits. The SCA variance were greater than GCA variance for the traits viz., plant height, head diameter, seed yield/plant, stem diameter and 100 seed weight, which showed greater manifestation of non-additive gene action. Among the CMS line, BCB-43A and among the testers, LTRR-822, RHA-95C-1 and RHA-95C-2 were good general combiners for most ofthe traits. The cross combinations BCB-171A × RHA 95C-2, BCB-44A × RHA-92, BCB-44A × RHA-95C-1, BCB-43A × GKVK-2 and BCB-170A × LTRR-822 showed higher sca for seed yield/plant.